An Application and Contribution of Abduldaem Al-Kaheel’s Website towards Quranic Learning in the Perspective of Modern Science - Afandi, Lukman; Abd Razzak, Monika @ Munirah (Jurnal Usuluddin, 2019)
Abduldaem Al-Kaheel developed his own website that dedicated to emphasizing on learning the QurÄn in the perspective of modern science. This article elaborates on his contribution in learning verses of the QurÄn that are relevant to science using websites as platforms. The site discusses meaning of the verses that can be interpreted in the perspective of science, and then detailed explanations of the links between the verse and the scientific findings. The article concludes that the appreciation and understanding of the QurÄn through internet is an effective way that one could use as self-study or reference to deepen knowledge of the teaching of the QurÄn in the perspective of science. This article elaborates on methodology of Quranic interpretation through a scientific approach that focuses in relating certain verses to modern scientific findings.